Confined Synthesis of Oriented Two-Dimensional Ni3(hexaiminotriphenylene)2 Films for Electrocatalytic Oxygen Evolution Reaction - Liu, Xuan-He (Langmuir : the ACS journal of surfaces and colloids, 2020)
Metal-organic frameworks (MOFs) can provide atomically dispersed metal active coordination sites (M-NX, M-SX, and M-OX) for electrocatalytic reactions. Among them, MOFs with motif M-NX or analogues are expected to be promising active electrode materials for oxygen evolution reaction (OER). Contrary to bulk MOFs, two-dimensional (2D) MOFs usually have high surface areas, fully exposed active sites, and specific electrical properties. Herein, we constructed 2D Ni3(hexaiminotriphenylene)2 [Ni3(HITP)2] films on the electrode surface by utilizing the bottom-up liquid/liquid/gel tri-phase interface system and explored their potential applications in electrocatalytic OER. The thickness of the 2D Ni3(HITP)2 films can be controlled to be about 5 nm. The prepared 2D Ni3(HITP)2 films had oriented polycrystalline character and showed excellent performance in OER. A current density of 10 mA cm-2 for 3-layer Ni3(HITP)2 film electrodes was obtained at 1.62 V, which was 20 mV lower than that for the commercial IrO2 catalyst. Electrochemical tests and electrochemical impedance spectroscopy showed that better OER performance of 3-layer Ni3(HITP)2 films was ascribed to their high electrochemically active surface area, better kinetic process, and fast ion diffusion and transport